PENGARUH KEAHLIAN AUDITOR, SKEPTISISME PROFESIONAL AUDITOR DAN TEKANAN ANGGARAN WAKTU TERHADAP AUDIT JUDGMENT - Taufan, Januar; Ramadhani, Khair Maulana (LPPM Universitas Bina Bangsa, 2025)
This research aims to examine and analyze the effect of auditor expertise, auditors' professional skepticism and time budget preasure, on audit judgment. This research belongs to the type of quantitative research. The data collection methods used are primary data with field survey methods. The technique used is by distributing questionnaires to 67 respondents of external auditor who work at the Public Accounting Firm in the South Jakarta area. The sampling technique used is non-probability sampling. Testing this research data is processed using SPSS Version 27. The results of this study indicate partially that the auditor expertise has a positive and significant effect on audit judgment, auditors' professional skepticism has positive and significant effect on audit judgment, and time budget preasure has positive and significant effect on audit judgment.